Threats of Disease Spillover from Domestic Dogs to Wild Carnivores in the Kanha Tiger Reserve, India - Chaudhary, Vratika (Clemson University Libraries, 2016)
Many mammalian carnivore species persist in small, isolated populations as a result of habitat destruction, fragmentation, poaching, and human conflict. Their small numbers, limited genetic variability, and increased exposure to domestic animals such as dogs place them at risk of further losses due to infectious diseases. In India, dogs ranging from domestic to feral are associated with villages in and around protected areas, and may serve as reservoirs and vectors of pathogens to the carnivores within. India’s Kanha Tiger Reserve (KTR) is home to a number of threatened and endangered mammalian carnivores including tigers (Panthera tigris), leopards (Panthera pardus), wolves (Canis lupus), and dhole (Cuon alpinus). It also contains hundreds of small villages with associated dog populations, and my goal was to determine whether these dogs pose a disease threat to KTR's wild carnivores. In the summer of 2014 and again in the winter of 2015 I estimated the density of dogs in villages of varying sizes and distances from KTR's core zone, and the exposure of these dogs to four pathogens that could threaten wild carnivores: rabies, canine parvovirus (CPV), canine distemper (CDV), and canine adenovirus (CAV). Dog population densities ranged from 3.7 to 23.7/km2 (14 to 45 dogs/village), and showed no systematic variation with village area or human population size. These dog populations grew in all villages between the summer of 2014 and winter of 2015, primarily through reproduction. No dog tested positive for rabies but I found high levels of seroprevalence to the other three pathogens: CPV (83.6% in summer 2014, 68.4% in winter 2015), CDV (50.7% in summer 2014, 30.4% in winter 2015) and CAV (41.8% in summer 2014, 30.9% in winter 2015). The declines in seroprevalence between summer and winter were primarily due to births in the population, of animals not exposed to the viruses. I opportunistically documented interactions between the dogs and wild carnivores that might allow disease transmission. I measured these ...